In-hospital outcomes predictors and trends of redo sternotomy aortic root replacements: insights from a UK registry analysis - Fudulu, Daniel P.; Dong, Tim; Kota, Rahul; Sinha, Shubhra; Chan, Jeremy; Rajakaruna, Cha; Dimagli, Arnaldo; Angelini, Gianni D.; Ahmed, Eltayeb Mohamed (Frontiers in Cardiovascular Medicine, 2024)
Redo sternotomy aortic root surgery is technically demanding, and the evidence on outcomes is mostly from retrospective, small sample, single-centre studies. We report the trend, early clinical results and outcome predictors of redo aortic root replacement over 20 years in the United Kingdom.We retrospectively analysed collected data from the UK National Adult Cardiac Surgery Audit (NACSA) on all redo sternotomy aortic root replacements performed between 30 th January 1998 and 19 th March 2019. We analysed trends in the volume of operations, characteristics of hospital survivors versus non-survivors, and predictors of in-hospital outcomes.During the study period, 1107 redo sternotomy aortic root replacements were performed (median age 59, 26% of patients were females). Eighty-four per cent of cases (N=931) underwent a composite root replacement, 11% (N=119) had homograft root replacement and valve-sparing root replacement was performed in 5.1% (N=57) of cases. There was a steady increase in the volume of redo sternotomy root replacements beyond 2006, from an annual volume of 22 procedures in 2006 to 106 procedures in 2017. Hospital mortality was 17% (n=192), postoperative stroke or TIA occurred in 5.2% (n=58), and postoperative dialysis was required in 11% (n=109) of patients. Return to the theatre for bleeding/tamponade was required in 9% (n=102) and median in-hospital stay was 9 days.